Properties of locally available river dredged soil stabilized with cement - Hossain, MB; Barman, Z; Dey, M (Progressive Agriculture, 2021)
In Bangladesh, the topsoil of agricultural land is being used to manufacture burnt clay bricks for a long time. This is one of the major reasons for reducing the cultivable land every year. But, we have a huge amount of River Dredged Soil (RDS) available that could be used for manufacturing building materials as an alternate to the conventional bricks. In this regard, the present study has been performed to investigate various properties of RDS from the Brahmaputra River and different mixes of RDS containing different percentages of cement content. The physical properties such as specific gravity, unit weight, mean diameter, maximum dry density and optimum moisture content of RDS were determined following standard procedures. Cylindrical specimens of RDS were prepared by mixing with different amounts of cement content. All the specimens were cured for 7, 14, and 28 days before testing. Water absorption of the RDS-cement specimens after 28 days was found between 14 to 18% which is in the range of first-class burnt clay brick. It was found that the water absorption decreases with the increase in the percentages of cement content. The unconfined compressive strength was observed to increase with the increment of cement content as well as curing age. The maximum unconfined strength was recorded for the specimens containing 14% cement and the rate of strength increment was about 45% in two weeks. It means the addition of cement with RDS will definitely increase the strength. But, the maximum use of cement must be decided based on the required strength and economic consideration. The deformation at failure was found decrease with the increase in cement content. This indicates that the stiffness of the stabilized RDS would increase upon the increment of cement content. Based on the above test results, it is concluded that the dredged soil from Brahmaputra River can be stabilized with cement for making compressed earth block which would be an alternative to the burnt clay brick that uses valued agricultural soil as raw material. Progressive Agriculture 32 (1): 71-77, 2021